The Electricity Sector in FYR Macedonia - Tieman, Alexander (IMF Working Papers; Working Paper, 2011)
This paper describes the current state of the Macedonian electricity sector. It looks at ongoing structural changes, driven by the gradual adoption of the EU acquis on energy, and comes up with estimates for electricity subsidies. It concludes by discussing the longer term outlook and sketching policy options.